Sogana from the Greater Sunda (Hemiptera: Fulgoromorpha: Tropiduchidae) - Constant, Jerome (Zootaxa, 2010)
A new species of Sogana Matsumura, 1914, S. floreni n. sp., is described from Borneo, Sabah (Malaysia). The species is compared with S. robustocarina Liang & Wang, 2008 and S. stimulata Melichar, 1914, and an addendum to the key to the species of Sogana by Liang & Wang (2008) is given to place the new species. Male genitalia and habitus are illustrated, biological data are provided. A distribution map is given for the 3 species of Sogana known from the Greater Sunda.